A Multi-Technique Analysis of Surface Materials From Blood Falls, Antarctica - Sklute, Elizabeth C.; Mikucki, Jill A.; Dyar, M. Darby; Lee, Peter A.; Livi, Ken J. T.; Mitchell, Sarina (Frontiers in Astronomy and Space Sciences, 2022)
Aperiodic discharge of brine at Blood Falls forms a red-tinged fan at the terminus of Taylor Glacier, Antarctica. Samples from this discharge provide an opportunity for mineralogical study at a Martian analogue study site. Environmental samples were collected in the field and analyzed in the laboratory using Fourier transform infrared, Raman, visible to near-infrared, and Mössbauer spectroscopies. Samples were further characterized using microprobe and inductively coupled plasma optical emission spectroscopy for chemistry, and x-ray diffraction, scanning electron microscopy, and transmission electron microscopy for mineralogy, crystallography, and chemistry. The mineralogy of these samples is dominated by the carbonate minerals calcite and aragonite, accompanied by quartz, feldspar, halide, and clay minerals. There is no strong evidence for crystalline iron oxide/hydroxide phases, but compositionally and morphologically diverse iron- and chlorine-rich amorphous nanospheres are found in many of the samples. These results showcase the strengths and weaknesses of different analytical methods and underscore the need for multiple complementary techniques to inform the complicated mineralogy at this locale. These analyses suggest that the red color at Blood Falls arises from oxidation of dissolved Fe2+ in the subglacial fluid that transforms upon exposure to air to form nanospheres of amorphous hydroxylated mixed-valent iron-containing material, with color also influenced by other ions in those structures. Finally, the results provide a comprehensive mineralogical analysis previously missing from the literature for an analogue site with a well-studied sub-ice microbial community. Thus, this mineral assemblage could indicate a habitable environment if found elsewhere in the Solar System.